Cloning and Expression of Recombinant Human Endostatin in Periplasm of Escherichia coli Expression System - Abbas Mohajeri; Yones Pilehvar-Soltanahmadi; Mohammad Pourhassan-Moghaddam; Jalal Abdolalizadeh; Pouran Karimi; Nosratollah Zarghami (Tabriz University of Medical Sciences, 2016)
Purpose: Recombinant human endostatin (rhEs) is an angiogenesis inhibitor which is used as a specific drug in the treatment of non-small-cell lung cancer. In the current research, we developed an efficient method for expressing soluble form of the rhEs protein in the periplasmic space of Escherichia coli via fusing with pelB signal peptide. Methods: The human endostatin (hEs) gene was amplified using synthetic (hEs) gene as a template; then, cloned and expressed under T7 lac promoter. IPTG was used as an inducer for rhEs expression. Next, the osmotic shock was used to extraction of protein from the periplasmic space. The presence of rhEs in the periplasmic space was approved by SDS-PAGE and Western blotting. Results: The results show the applicability of pelB fusion protein system usage for secreting rhEs in the periplasm of E. coli in the laboratory scale. The rhEs represents approximately 35 % (0.83mg/l) of the total cell protein. Conclusion: The present study apparently is the ﬁrst report of codon-optimized rhEs expression as a fusion with pelB signal peptide. The results presented the successful secretion of soluble rhEs to the periplasmic space.